2017
DOI: 10.1186/s41120-017-0020-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of rates of nausea side effects for prescription medications from an online patient community versus medication labels: an exploratory analysis

Abstract: Background: While medication labels are considered the authoritative resource for medication information, emerging research suggests that patient-generated health data (PGHD) are a valuable tool to understand the ways in which patients experience medications in real world settings. However, the relationship between these two data sources has not been closely examined. Methods: To understand how rates of medication side effects compare between a source of PGHD and medication labels, the current study compares a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Many of the publications state that similar patterns of adverse events were reported in social media as compared to other traditional pharmacovigilance data sources [35-43, 47, 48, 51-56, 60-62, 64-70, 74-78, 82, 83, 85-89, 92, 94, 98, 99, 102-105]. However, some studies [24,45,46,50,57,59,62,89,94,102,103] detected fewer numbers of adverse events on social media.…”
Section: Results Of Comparisonmentioning
confidence: 89%
See 2 more Smart Citations
“…Many of the publications state that similar patterns of adverse events were reported in social media as compared to other traditional pharmacovigilance data sources [35-43, 47, 48, 51-56, 60-62, 64-70, 74-78, 82, 83, 85-89, 92, 94, 98, 99, 102-105]. However, some studies [24,45,46,50,57,59,62,89,94,102,103] detected fewer numbers of adverse events on social media.…”
Section: Results Of Comparisonmentioning
confidence: 89%
“…Interestingly, two studies [21] noted the number of new ADEs identified in social media was higher than with SIDER. However, fewer new ADEs are identified in social media if a comparison is made to more uptodate sources such as clinicaltrials.gov, FDA data and Pubmed or MEDLINEPlus 46 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies indicated that OHC increased patient empowerment which consequently improved health outcomes [ 39 ]. Additionally, the studies also address various themes and perspectives such as patient perception [ 40 ], patients reported outcomes (PROs) [ 41 ], crowdsourcing, patient-centeredness [ 42 , 43 ], pharmacovigilance and adverse drug reactions reporting [ 44 ], drug development process [ 45 ] and off-label prescribing [ 46 ].…”
mentioning
confidence: 99%